Rationalizing the Regioselectivity of Azolation of Benzylic C–H Bonds under Photoredox Catalysis - Sanosa, Nil; Montiel-Cervantes, César; Rubio-Muñoz, Miguel; Sampedro, Diego; Funes-Ardoiz, Ignacio (Synlett, 2024)
A density functional theory (DFT) study was performed to evaluate the reaction mechanism of the C–N bond formation under an integrated hydrogen atom transfer/radical-polar crossover photoredox catalytic cycle. The regioselective activation of a model substrate, including three reactive positions (3° benzylic C–H bond, 2° benzylic C–H bond, and primary C–Cl bond) was addressed to distinguish among the radical C–H activation mechanism and the standard SN2 reaction. We demonstrated that activation of tertiary benzylic C–H bond is the most favored and forms exclusively the experimentally observed product. In addition, the whole photoredox catalytic cycle, including the outer-sphere electron-transfer steps, was characterized computationally.
Keywords: photoredox catalysis; C–N bond formation; density functional theory; regioselectivity; reaction mechanism